2016
DOI: 10.3109/0886022x.2016.1163998
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effect of naringin in acetaminophen-induced hepatic and renal toxicity in laboratory rats: role of FXR and KIM-1

Abstract: Naringin exerts its hepato- and nephroprotective effect via modulation of oxido-nitrosative stress, FXR and KIM-1 mRNA expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 85 publications
(89 reference statements)
5
51
0
1
Order By: Relevance
“…Thus, ANTU‐induced toxicity is also associated with hepatic damage . AST and ALT are the two important hepatic enzymes documented to be elevated during the hepatic injury . In the present investigation, ANTU administration caused a significant elevation in serum AST and ALT levels confirming hepatic damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, ANTU‐induced toxicity is also associated with hepatic damage . AST and ALT are the two important hepatic enzymes documented to be elevated during the hepatic injury . In the present investigation, ANTU administration caused a significant elevation in serum AST and ALT levels confirming hepatic damage.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of messenger RNA (mRNA) were analyzed in the lung, pulmonary artery, and RV tissues ( n = 4) using the reverse‐transcriptase polymerase chain reaction (RT‐PCR) approach as described previously . Briefly, single‐stranded complementary DNA was synthesized from 5 µg of total cellular RNA using reverse‐transcriptase (MP Biomedicals India Private Limited, Mumbai, India), as described previously .…”
Section: Methodsmentioning
confidence: 99%
“…The levels of mRNA were analyzed in sciatic nerve using a reverse transcription (RT)- Polymerase chain reaction (PCR) approach as described previously (Adil et al, 2016[3], 2014[5]). Single-stranded cDNA was synthesized from 5 µg of total cellular RNA using reverse transcriptase (MP Biomedicals India Private Limited, India) as described previously (Adil et al, 2014[5]; Ketkar et al, 2015[51]).…”
Section: Methodsmentioning
confidence: 99%
“…The altered serum creatinine level is one of the important clinical features of CIN that has been consistently ob-served in the available body of evidence (18,32). It has been well documented that the increased level of ROS induces mesangial cells contraction and modifies the filtration surface area, resulting in an increased serum creatinine level (33,34). Previous preclinical studies suggested that antioxidant supplementation inhibits free radical damage and thereby decreases GFR and finally inhibits CIN-induced el-6…”
Section: Discussionmentioning
confidence: 99%